Real-world Global Outcomes of Retrograde Intrarenal Surgery in Anomalous Kidneys: A High Volume International Multicenter Study - TANIDIR, YILÖREN (Elsevier Inc., 2021)
Objective: To analyze the trends and outcomes of retrograde intrarenal surgery for treatment of urolithiasis in anomalous kidneys in a large international multicenter series. Materials and Methods: We designed a multicentric retrospective study. Nineteen high-volume centers worldwide were included. Pre-, peri- and postoperative data were collected, and a subgroup analysis was performed according to renal anomaly. Results: We analyzed 414 procedures: 119 (28.7%) were horseshoe kidneys, 102 (24.6%) pelvic ectopic kidneys, 69 (16.7%) malrotated kidneys and 50 (12.1%) diverticular calculus. The average size (SD) of the stone was 13.9 (±6) millimeters and 193 (46.6%) patients had a pre-operative stent. In 249 cases (60.1%) a disposable scope was used. A UAS (ureteral access sheath) was used in 373 (90%) patients. A Holmium laser was used in 391 (94.4%) patients. The average (SD) operating time was 65.3 (±24.2) minutes. Hematuria, caliceal perforation and difficulty in stone localisation were mostly seen in diverticular stones and difficulty in UAS placement and lithotripsy in the cases of renal malrotation. The overall complication rate was 12%. Global stone-free rate was 79.2%. Residual fragments (RF) were significantly lesser in the pre-stented group (P <.05). Diverticular calculi was the group with more RF and needed ancillary procedures (P <.05). Conclusion: Retrograde intrarenal surgery in patients with anomalous kidneys is safe and effective with a high single-stage stone-free rate and low complication rate. There is a trend toward using smaller and disposable scopes and smaller UAS. Diverticular stones can still be challenging with higher rates of intraoperative hematuria, caliceal perforation and RF. © 2021 Elsevier Inc.